Born of gilded mountains : a novel - Dykes, Amanda (Bethany House, a division of Baker Publishing Group, 2024)
"Scandal-plagued Hollywood star Mercy Windsor seeks refuge in the Colorado mining town where her childhood pen pal lived. To help a grieving friend, Mercy embarks with her on a search for a missing railcar, hoping the mailbag it contains clears her friend's family name and points the way to a rumored gold mine."--